(untitled) (Indian Journal of Veterinary Pathology, 2025)
The study was conducted on blood samples of dogs to correlate the erythrocytic abnormalities with leukogram and cytological findings. The study was conducted on blood samples submitted to Centralized Clinical Diagnostic Laboratory in the Department of Teaching Veterinary Clinical Complex, Guru Angad Dev Veterinary and Animal Sciences University (GADVASU) Ludhiana. The Leukogram analysis was carried out in all the 363 cases and detailed leukocytic abnormalities were recorded. The cases were categorized into those having normal total leukocyte count, leukopenia, leukocytosis and finally the cases having leukemoid response. On the basis of cytological examination, the cases were classified into neoplastic and non-neoplastic conditions. A good correlation was between presence of codocytes, schistocytes, echinocytes, polychromatophilic RBCs and leukocytosis and stomatocytes and polychromatophilic RBCs with leukopenia. In addition, acanthocytes, echinocytes and schistocytes were common in cases of lymphoma.